Оценка надежности деятельности операторов в системах предоставления доступа к ресурсам компьютерных сетей - Криводуб, Анна Сергеевна (НТУ "ХПИ", 2016)
Рассматриваются телекоммуникационные системы, специализирующиеся на предоставлении ИТ-услуг населению и организациям. Описывается деятельность операторов технической поддержки, направления на устранение возможных проблемных ситуаций. Обоснована целесообразность использования для формализации деятельности функционально-структурной теории эрготехнических систем профессора Анатолия Ильича Губинского. Приведены примеры формализованных описаний деятельности операторов по устранению некоторых проблем предоставления ИТ-услуг. Приведен пример расчета вероятности своевременного и безошибочного выполнения алгоритма деятельности по устранению одной из возможных проблемных ситуаций.

The purpose of the article is the development of formalized models and algorithms for estimating the activity of operators working in telecommunication systems, specializing in providing IT services to the population and companies. The generalized structural method of the functional and structural theory of ergonomic and technical systems of professor A. I. Gubinsky is chosen as a basic solving method. The method is based on the use of standard functional units to describe the algorithms of activity. These units are presented in the form of functional networks. A number of formalized descriptions of algorithms of the operators’ activities for elimination of some problems of IT services providing is developed. The calculations of probability of timely and faultless execution of the activities algorithm for the elimination of one of possible problem situations are performed. The technology of the account at an assessment of reliability of activities for elimination of problems is shown.
The approach to the evaluation of options of the activities of the operators technical support information services telecommunication systems
Keywords: эргономика; человек-оператор; алгоритм деятельности; рабочее место; условия труда; ergonomics; human operator; activity algorithm